Erasable serum markers - Shirin Nouraein; Honghao Li; Sangsin Lee; Vidal A. Saenz; Emma K. Raisley; Sho Watanabe; Vincent D. Costa; Jerzy O. Szablowski (Proceedings of the National Academy of Sciences, 2025)
Gene expression in the brain is typically evaluated using invasive biopsy or postmortem histology. Serum markers provide an alternative way to monitor the brain, but relatively few such markers exist. Additionally, the origin of serum markers often cannot be localized to a specific cell population, and monitoring dynamic changes in their gene expression is compromised by the same factor that makes the markers detectable—long serum half-life. Here, we propose a paradigm to improve the sensitivity of serum marker measurement by modifying them with an external chemical stimulus. As a proof of concept, we use a well-controlled system with known half-life and tunable serum levels. This system, released markers of activity (RMA), or RMAs enables measurement of transgene expression in the brain through a simple blood test. RMAs are stable in blood, with a half-life of >100 h and can detect expression from as few as 12 neurons in mice. However, their long serum half-life also generates detectable background signals when RMA are used to track temporal changes in gene expression. By engineering on-demand erasable RMAs and injecting an intravenous targeted protease, we reduced RMA background signal by more than an order of magnitude without compromising the detection sensitivity. Similarly to previous RMA iterations, our approach showed a 65,000-fold increase in their signal over the baseline when expressed in a single brain region but also improved the dynamic range of detection for low-level promoter activity that is driven by physiological levels of c-Fos.